Going Green: Exploring the Factors Behind Eco-Friendly Products Purchase Intentions - Siagian, Hendra Sakti Putra; Khair, Hazmanan; Jufrizen, Jufrizen; Tirtayasa, Satria; Rahmat, Muhammad (Journal of International Conference Proceedings, 2025)
Unregulated worldwide consumption habits have resulted in significant issues such as pollution and climate change, hence underscoring the necessity for understanding of eco-friendly products. This study seeks to examine the impact of students' awareness of eco-friendly products on their intention to acquire such products. This study specifically investigates the impact of awareness, availability, value, and quality on students' desire to purchase reusable bottled water products, as well as how these characteristics predict purchase intention among students. Data were gathered through an online survey of 145 students from diverse universities in Indonesia and analyzed utilized partial least squares-structural equation modelling (PLS-SEM). The findings revealed that awareness and perceived value significantly enhance the purchase intention of reusable bottled water products, with perceived value being the most influential element. These findings underscore the necessity of enhancing awareness and value the of eco-friendly products to promote more sustainable and responsible consumption among students, thereby significantly contributing to environmental conservation initiatives and the reduction of plastic waste in society. Furthermore, these findings offer valuable insights for stakeholders in formulating more successful marketing strategies to enhance student engagement in sustainable consumption.